2008
DOI: 10.1523/jneurosci.0309-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Requirements in Axonal Transport of Slow Component-b

Abstract: Slow component-b (SCb) translocates ϳ200 diverse proteins from the cell body to the axon and axon tip at average rates of ϳ2-8 mm/d. Several studies suggest that SCb proteins are cotransported as one or more macromolecular complexes, but the basis for this cotransport is unknown. The identification of actin and myosin in SCb led to the proposal that actin filaments function as a scaffold for the binding of other SCb proteins and that transport of these complexes is powered by myosin: the "microfilament-complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 50 publications
(67 reference statements)
3
65
0
Order By: Relevance
“…Unless otherwise specified, tissue culture reagents were obtained from Invitrogen/Gibco. Neurons preparation followed standard protocols (Kaech and Banker, 2006;Roy et al, 2008). Briefly, cortical tissue was dissected from brain and dissociated in Hank's balanced salt solution (HBSS), 0.25% trypsin, and DNAaseI (Worthington Biochemical Corp.), then incubated for 30 minutes at 37˚C.…”
Section: Primary Neuron Culturesmentioning
confidence: 99%
“…Unless otherwise specified, tissue culture reagents were obtained from Invitrogen/Gibco. Neurons preparation followed standard protocols (Kaech and Banker, 2006;Roy et al, 2008). Briefly, cortical tissue was dissected from brain and dissociated in Hank's balanced salt solution (HBSS), 0.25% trypsin, and DNAaseI (Worthington Biochemical Corp.), then incubated for 30 minutes at 37˚C.…”
Section: Primary Neuron Culturesmentioning
confidence: 99%
“…In this case, the transport is mediated by specialized isoforms of cytosolic dyneins that are associated with the protein complex dynactin (73,74). Early publications suggested that slow anterograde transport requires microfilament networks as scaffolds; however, more recent studies indicate that microtubules play a critical role (21,221). Metabolic enzymes, including GAPDH, are delivered to axons and dendrites with the slow anterograde transport in macromolecular complexes with cytoskeletal proteins.…”
Section: Defects In Axonal and Dendritic Transportmentioning
confidence: 99%
“…In 2007, Woods et al described several new protein partners of -synuclein by phage display and NMR spectroscopy, and among them a key protein implicated in the regulation synaptic vesicle release was identified: synapsin 1a. As a further indication of the occurrence of -synuclein-synapsin 1 interaction, it has been shown that these two proteins are cotrasportated from the cell body to the axon by the slow component-b (Roy et al, 2007;Roy et al, 2008). These observations were lately confirmed by other findings indicating thatsynuclein transgenic overexpression results in a significant reduction of synapsin 1, thus impairing vesicle reclustering after exocytosis .…”
Section: The α-Synuclein Synaptic Proteomementioning
confidence: 69%
“…Furthermore, synapsin 1 and -synuclein share numerous functional and biochemical similarities. Indeed, besides being both part of the DAT (Maiya et al, 2007) and synaptic proteome (Burre and Volknandt, 2007), they are co-transported from the cell body to the axon by the slow component b as multiprotein complexes without being affected by actin depletion (Roy et al, 2007;Roy et al, 2008) and they can bind to synaptic vesicles and interact with presynaptic membranes and actin cytoskeleton, modulating the dynamics of the actin-based network during the exo-endocytotic cycle (Cesca et al, 2010;Tofaris and Spillantini, 2007). Noteworthy, despite their different localization in subregions of the adult brain (Pieribone et al, 2002;Cesca et al, 2010) synapsin 1 and 3 share a strong structural homology in their functional domains (Hosaka and Sudhof, 1998), suggesting that they may likely interact with similar proteins and cytoskeletal components, although they differentially regulate neurotransmitter release (Kile et al, 2010;Feng et al, 2002;Cesca et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%